2019
DOI: 10.1017/wsc.2019.5
|View full text |Cite
|
Sign up to set email alerts
|

Target site–based penoxsulam resistance in barnyardgrass (Echinochloa crus-galli) from China

Abstract: Barnyardgrass [Echinochloa crus-galli (L.) P. Beauv.] is acknowledged to be the most troublesome weed in rice fields in Anhui and Jiangsu provinces of China. It cannot be effectively controlled using certain acetolactate synthase (ALS)-inhibiting herbicides, including penoxsulam. Echinochloa crus-galli samples with suspected resistance to penoxsulam were collected to identify the target site–based mechanism underlying this resistance. Populations AXXZ-2 and JNRG-2 showed 33- and 7.3-fold resistance to penoxsul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 31 publications
1
44
0
Order By: Relevance
“…Penoxsulam-resistant Echinochloa spp. were reported in various rice-growing regions of China, including Jiangsu, Anhui, Hubei, Hunan, Jiangxi, and Heilongjiang provinces (Chen et al 2016;Fang et al 2019a;Liu et al 2019;Yang et al 2013). Xia et al (2016) also reported E. crus-galli populations from Hubei Province that had developed resistance to the ACCase inhibitor metamifop.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Penoxsulam-resistant Echinochloa spp. were reported in various rice-growing regions of China, including Jiangsu, Anhui, Hubei, Hunan, Jiangxi, and Heilongjiang provinces (Chen et al 2016;Fang et al 2019a;Liu et al 2019;Yang et al 2013). Xia et al (2016) also reported E. crus-galli populations from Hubei Province that had developed resistance to the ACCase inhibitor metamifop.…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, it was demonstrated that any of the ALS gene copies could host the ALS-inhibitor resistance mutation (Deng et al 2017;, which may also be the reason why these weeds are prone to develop resistance to ALS inhibitors. The Ala-122-Gly/Asn, Ala-205-Val, Trp-574-Leu, and Ser-653-Asn mutations in ALS have been reported to confer resistance to ALS-inhibiting herbicides in E. crus-galli (Fang et al 2019a;Matzenbacher et al 2015;Panozzo et al 2013Panozzo et al , 2017. In addition, the NTSR mechanism was reported in various ALS inhibitor-resistant weeds, such as E. crus-galli, D. sophia, and giant chickweed [Myosoton aquaticum (L.) Moench] (Bai et al 2019;Fang et al 2019b;Yang et al 2016).…”
Section: Cloning and Sequence Analysis Of Als And Accase Genesmentioning
confidence: 99%
“…Barnyardgrass, an allohexaploid grass, has always been considered the most troublesome weed species in rice production in China (Fang et al 2018(Fang et al , 2019a(Fang et al , 2019b. Season-long competition of barnyardgrass can cause as much as 80% rice yield reduction (Ntanos and Koutroubas 2000;Smith 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the chance is high that barnyardgrass will become resistant to ALS inhibitors (Powles and Yu 2010). During the last decade, resistance to ALS-inhibiting herbicides has increased drastically in various cropping systems (Fang et al 2019a(Fang et al , 2019bHeap 2020;McCullough et al 2016aMcCullough et al , 2016bPowles and Yu 2010;Yu et al 2020a). To date, a total of 165 weed species worldwide have been found to be resistant to at least one of the five ALS inhibitor chemical families (Heap 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation